2022
DOI: 10.3390/ijms23148019
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Analyses and Antimicrobial Activity of Novel Ciprofloxacin and 7-Hydroxy-4-methylcoumarin, the Plant-Based Natural Benzopyrone Derivative

Abstract: Coumarin is highly distributed in nature, notably in higher plants. The biological features of coumarin include antibacterial, anticancer and antioxidant effects. It is well known that metal ions present in complexes accelerate the drug action and the efficacy of organic therapeutic agents. The main aim of the current study is the synthesis of different complexes of the interaction between ciprofloxacin hydrochloride (CIP) and coumarin derivative 7-hydroxy-4-methylcoumarin (HMC) with Zr(IV). The chelates of CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that 7H-4M and its derivatives possess several biological properties. Known as a potent xanthine oxidase inhibitor, 7-hydroxy 4-methylcoumarin is effective in inhibiting both the settlement as well as the byssogenesis of mussels, modulating some of the effector functions of human neutrophils and exhibiting antioxidant activity [ 22 , 23 , 24 , 25 ]. We previously reported that 7H-4M alleviates the LPS-induced inflammatory response in RAW264.7 macrophage cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 7H-4M and its derivatives possess several biological properties. Known as a potent xanthine oxidase inhibitor, 7-hydroxy 4-methylcoumarin is effective in inhibiting both the settlement as well as the byssogenesis of mussels, modulating some of the effector functions of human neutrophils and exhibiting antioxidant activity [ 22 , 23 , 24 , 25 ]. We previously reported that 7H-4M alleviates the LPS-induced inflammatory response in RAW264.7 macrophage cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sadeek et al demonstrated that compounds based on octahedral mixed-ligand complexes of Zr(IV) with ciprofloxacin hydrochloride as the primary ligand and 7-hydroxy-4-methylcoumarin as the secondary ligand with different coordination modes (CIP-HMC, Figure 23) possess promising biological activity against Gram-positive bacterial strains, including B. subtilis (MIC = 0.50-0.75 µg/mL) and B. cereus (MIC = 0.25-0.75 µg/mL), as well as Gram-negative bacterial strains, including P. aeruginosa (MIC = 0.50-1.0 µg/mL), K. pneumoniae (MIC = 0.50-1.0 µg/mL), and E. coli (MIC = 0.50-1.0 µg/mL), compared to the free ciprofloxacin (CP: G + ve bacterial strains MIC = 0.50 µg/mL, G − ve bacterial strains MIC = 0.5-0.75 µg/mL) and 7-hydroxy-4methylcoumarin (HMC: G + ve bacterial strains MIC = 0.25 µg/mL, G − ve bacterial strains MIC = 0.25-0.50 µg/mL). The chelation process accelerates the drug action, increasing the potency of both ciprofloxacin and coumarin molecules especially towards B. subtilis (diameter of inhibition zone: 48-66 mm vs. 18-26 mm) [103]. It should be mentioned that, in general, metal complexes are more active than their ligands and may serve as carriers to enhance the activity of ligands as the principal acting agents [101].…”
Section: Synthetic 7-hydroxycoumarin-based Compounds As Antibacterial...mentioning
confidence: 99%
“…It should be mentioned that, in general, metal complexes are more active than their ligands and may serve as carriers to enhance the activity of ligands as the principal acting agents [101]. Thereby, these new Zr(IV) complexes build attractive molecules for further studies to determine the efficient concentrations of coumarin derivatives in the complexes and their mode of action [103].…”
Section: Synthetic 7-hydroxycoumarin-based Compounds As Antibacterial...mentioning
confidence: 99%
“…Pseudomonas aeruginosa is a gram-negative bacterium that is widely distributed in nature [ 19 ]. It requires simple nutrition for growth, has strong adaptability to the natural environment, and can produce substances that promote biodegradation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%